Improved efficiency of DSSC using combustion synthesized TiO2 - Umale, Sanjivani; Sudhakar, V.; Sontakke, Sharad M.; Krishnamoorthy, K.; Pandit, Aniruddha B. (Materials Research Bulletin, 2019)
Combustion synthesis method is an economic, one step and an effective method for the synthesis of nanomaterials. In this work, titanium dioxide nanoparticles were synthesized by combustion method. The synthesized material was characterized by XRD, SEM and BET. Dye sensitized solar cell was fabricated using the synthesized material and its performance was compared with the solar cell fabricated using commercial TiO2. In order to evaluate the photovoltaic performance of DSSCs, photocurrent density to photovoltage (J-V) characteristic and electrochemical impedance spectroscopy (EIS) measurements were carried out. The DSSC fabricated using combustion synthesized and commercial TiO2 exhibited a power conversion efficiency of 6.11% and 6.62%, respectively. Combustion synthesized TiO2 which displayed similar efficiency to that of commercial material is least studied in the literature for solar cell applications.
Keywords: Combustion synthesis; Dye sensitized solar cell; TiO2